Forecasting of The Number of Schizophrenia Disorder by using The Box-Jenkins of Time Series Analysis - Syifa Putri Humaira; Indah Nursuprianah; Darwan Darwan (Journal of Robotics and Control (JRC), 2020)
Schizophrenia is a mental disorder with a complex brain disorder that causes sufferers not to be able to distinguish between reality and imagination. This study aims to determine the parameters for the best model Box-Jenkins time series analysis in predicting the number of schizophrenic in Cirebon City in 2018 as seen from the smallest MSE (Mean Square Error) value. This study uses Box Jenkins method (often referred to as the ARIMA Method) with documentation collection techniques and literature studies. The documentation aims to collect data on the number of schizophrenic patients in January 2014 to December 2018. Data were analyzed in several stages, namely the stage of data stationary identification, determining model parameter estimates, model verification and forecasting. The results of this study show that the best model for predicting the number of schizophrenic patients in the future is ARIMA (0,1,1). The forecasting results of the number of schizophrenic patients in Cirebon City from January to December 2018 respectively are 69 people, 68 people, 68 people, 68 people, 68 people, 68 people, 67 people, 67 people, 67 people, 67 people, 67 people, 67 people.